PREPARATION OF NI-MO CATALYSTS USING THE PILLARED CLAY AS A SUPPORT FOR HYDRODESULFURIZATION OF COKER NAPHTHA - Nino Rinaldi (Widyariset, 2011)
On the preparation of the Ni-Mo catalysts, a high of surface area of the support was needed in order to achieve the well dispersion of Mo on the support. One of the promising ways is the use of pillared clays as the support. Therefore, the preparation of pillared clay for a support of Ni-Mo catalyst and its effect on the hydrodesulfurization (HDS) reaction for sulfur removal of Coker naphtha were studied. The effects of pH of the Mo impregnation solutions were also studied. The results show that the pillarization process on clay using Al-pillared is signiﬁ  cantly increased the surface area. Moreover, with the pH of the impregnation solution of 10, Mo is higher dispersed on the pillared clay support compared to pH-1, and thus the HDS activity of NiMo pillared clay catalyst of pH-10 is also more active. However, the HDS activity of the present catalysts is still not good enough compared to the commercial NiMo catalyst.